DESENVOLVIMENTO E APLICAÇÃO DE UM KIT EXPERIMENTAL COM ARDUINO PARA O ENSINO DO ELETROMAGNETISMO. - NUNES, Heberval Moreira (2018)
Currently, there is more and more use of technologies in high-school classrooms is increasingly seen as a teaching and learning process, mainly due to the spread of computers and interactive programs. The possible educational technologies that can be used and the pedagogical proposals can be used, highlighting in this work the use of didactic experiments in physics classes and also in a methodological proposal that was presented as a pedagogical activity. In this proposal, the use of technology as a tool to enhance the teaching of Electromagnetism. The proposal developed is an experimental kit produced with low-cost materials associated with a platform of automatic data acquisition and interpretation called Arduino, both controlled, from a distance, by Bluetooth, for an application, built on a platform of free software development. With this proposal, related hardware and software prototyping platforms to demonstrate that a coil generates your current driving around a magnetic induction field and also to observe the Joule effect due to the passage of electric current by driver. The contextualization of the experimental activity proposal as pedagogical practice was planned following the humanist ideas of Novak and the theory of meaningful learning in the view of Marco Antonio Moreira. As pedagogical proposal assessment mechanism, have been applied some questionnaires to students, in which we found that most of them proved to be satisfied with the practice, because it allowed an indication of a significant learning of studied concepts.